Construction and test of a tungsten/Sci-Fi imaging calorimeter for the CREAM experiment - MARROCCHESI, P. S.; AHN, H. S.; BAGLIESI, M. G.; BASTI, A.; BIGONGIARI, G.; CASTELLINA, A.; GANEL, O.; LEE, M. H.; LOMTADZE, T.; LUTZ, L.; MAESTRO, P.; MALININE, A.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2004)
Cosmic Ray Energetics And Mass (CREAM) is a balloon-borne experiment designed to perform direct measurements of cosmic ray composition over the elemental range from proton to iron to the supernova energy scale of 1015 eV in a series of balloon flights using the new Ultra Long Duration Balloon (ULDB) capability under development by NASA. The first flight of CREAM will take place at the end of 2004 from Antarctica. The instrument includes a sampling tungsten/scintillating fiber calorimeter preceded by a graphite target with scintillating fiber hodoscopes, a pixelated silicon charge detector, a transition radiation detector and a segmented timing-based particlecharge detector. The thin ionization calorimeter has been designed to operate in the range of energies from a few hundred GeV to 1 PeV providing imaging capability in the reconstruction of the showers originating from the interaction of primary nuclei in the carbon target. A twin calorimeter for the second CREAM payload has been built and tested at CERN. Its construction technique and preliminary test results are presented.